2021
DOI: 10.3390/jmse9060643
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability and Trends of Marine Heat Waves in the Eastern Mediterranean Sea over 39 Years

Abstract: Marine heatwaves (MHWs) can cause devastating impacts on marine life. The frequency of MHWs, gauged with respect to historical temperatures, is expected to rise significantly as the climate continues to warm. The MHWs intensity and count are pronounced with many parts of the oceans and semi enclosed seas, such as Eastern Mediterranean Sea (EMED). This paper investigates the descriptive spatial variability and trends of MHW events and their main characteristics of the EMED from 1982 to 2020 using Sea Surface Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 60 publications
5
32
1
Order By: Relevance
“…The period (14-years) that we have used to derive the temperature baseline, instead of using a longer dataset, may have underestimated the number of MHWs detected over the AIC Seas. However, the computed numbers and the durations of the MHWs agree with the levels derived from other studies for the broader Mediterranean Sea (e.g., the modeling study by Darmaraki et al [19]: an increase of 1.7 events/decade; satellite observations by Ibrahim et al [18]: an increase of 1.2 events/decade). Moreover, the high-resolution of the SST data (0.01 • ) provided significant information about the spatial distribution of both MHWs and the SST trends over the study domain, following a recommendation by Hobday et al [24].…”
Section: Summary and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The period (14-years) that we have used to derive the temperature baseline, instead of using a longer dataset, may have underestimated the number of MHWs detected over the AIC Seas. However, the computed numbers and the durations of the MHWs agree with the levels derived from other studies for the broader Mediterranean Sea (e.g., the modeling study by Darmaraki et al [19]: an increase of 1.7 events/decade; satellite observations by Ibrahim et al [18]: an increase of 1.2 events/decade). Moreover, the high-resolution of the SST data (0.01 • ) provided significant information about the spatial distribution of both MHWs and the SST trends over the study domain, following a recommendation by Hobday et al [24].…”
Section: Summary and Discussionsupporting
confidence: 88%
“…The along-shore variability and interannual trends of the entire coastal region, which is of great social and ecological importance, will also be discussed for the first time. The findings of Inrahim et al [18], between 1982 and 2020, have shown that over the Eastern Mediterranean, the marine heat wave (MHW) frequency increased by 1.2 events per decade, with a maximum significant MHW SST event (6.35 • C above the 90th SST climatology threshold) in 2020. They related this increase to a decrease in the wind stress, an increase in the air temperature, and to an increase in the mean sea level pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also highlighted the strong spatial variability in SST trend estimations. Trend values over 1982-2020 have been estimated at 0.032 and 0.044 ± 0.002 • C/year as averages in the western and eastern Mediterranean, respectively (Juza and Tintoré, 2021), and at 0.033 ± 0.004 • C/year in the Ionian and Levantine Seas (Ibrahim et al, 2021). The rapid sea surface warming trend in this ocean basin has been associated with strong increase in MHW days, particularly during the last two decades since the beginning of the 20th century (Bensoussan et al, 2019;Ibrahim et al, 2021;Juza and Tintoré, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…Regardless of the mechanisms that drive individual MHWs, there is a growing acceptance that anthropogenic climate change has raised the likelihood of recent MHWs dramatically, including the following occasions. Prominent occasions occurred over the Red Sea, especially: in its northern basin, as stated by Chaidez et al [5]; in the Gulf of Aqaba, as stated by Shaltout [6]; along the Mediterranean Sea including the central Ligurian Sea (Sparnocchia et al [2]), the central basin (Olita et al [7]) and the eastern basin (Ibrahim et al [8]); over the eastern Indian ocean, especially along the Western Australian coast (Pearce and Feng [9]) and across northern Australia (Benthuysen et al [10]); over the northeastern Pacific ocean (Bond et al [11]); over the northwestern Atlantic ocean (Chen et al [12]). These occasions resulted in significant environmental and financial impacts, including a reduced chlorophyll-a concentration (Bond et al [11]), continuous coral bleaching (Hughes et al [13]), the death of fish (Caputi et al [14]), mass mortality (Garrabou et al [15]), geographical and seasonal shifts of marine species (Mills et al [16]; Cavole et al [17]) and economic problems (Mills et al [16]).…”
Section: Introductionmentioning
confidence: 93%